Sustainable Green Industry Work: Recovery of Copper Slag with Mill Scale Leaching Reactant Optimized by Response Surface Methodology (RSM) - Nizamoglu, Hasan; Turan, Mehmet Deniz; Sari, Zeynel Abidin; Babayeva, Pervane (Springer, 2024)
Copper slag (Cu:6.74%, Fe:36.45%) and mill scale (Fe:67.67) contain significant amounts of recoverable metals. This study consists of a two-stage experimental process. In the first stage, the mill scale was leached with hydrochloric acid (HCl) to obtain an iron chloride solution using the experimental method designed by Response Surface Methodology (RSM). In the second stage, the using conditions of this solution in the extraction of copper from copper slag were investigated. In the first stage, the experiments designed by RSM were carried out under atmospheric conditions by mechanical stirring with a two-bladed teflon stirrer. Under optimum conditions, iron dissolution, Fe (III)/Fe (II) ratio, and total iron concentration were found to be 93.99%, 5.45, and 16.44 mg/L, respectively. The Fe (III)/Fe (II) solution was accumulated for the second stage. In the second stage, the extraction of copper from copper slag by using the obtained solution was carried out in erlenmeyer flasks with a digitally controlled jacketed heating-magnetic stirrer unit. Under optimum conditions, 97.22% of copper was recovered. Additionally, for comparative purposes, experimental studies were conducted under the same conditions with a solution prepared in the presence of commercially obtained FeCl3 + HCl and only HCl, revealing that when only HCl was present, 75.05% of copper was passed into the solution, whereas when used in conjunction with commercial FeCl3 salt, 96.13% of copper was extracted. In conclusion, thanks to recycling, the waste mill scale in the leaching of copper slag can be used as an alternative to commercial products for green production.
Keywords: Copper slag; Mill scale; Hydrochloric acid; Leaching; RSM; Sustainability